Can Grit Be Taught? Lessons from a Nationwide Field Experiment with Middle-School Students - Indhira Santos; Violeta Petroska-Beska; Pedro Carneiro; Lauren Eskreis-Winkler; Ana Maria Munoz Boudet; Ines Berniell; Christian Krekel; Omar Arias; Angela Lee Duckworth (Institute of Labor Economics (IZA), 2022)
We study whether a particular socio-emotional skill – grit (the ability to sustain effort and interest towards long-term goals) – can be cultivated through a large-scale program, and how this affects student learning. Using a randomized control trial, we evaluate the first nationwide implementation of a low-cost intervention designed to foster grit and self- regulation among sixth and seventh-grade students in primary schools in North Macedonia (about 33,000 students across 350 schools). The results of this interventions are mixed. Exposed students report improvements in self-regulation, in particular the perseverance-of- effort facet of grit, relative to students in a control condition. Impacts on students are larger when both students and teachers are exposed to the curriculum than when only students are treated. For disadvantaged students, we also find positive impacts on grade point averages, with gains of up to 28 percent of a standard deviation one year post-treatment. However, while this intervention made students more perseverant and industrious, it reduced the consistency-of-interest facet of grit. This means that exposed students are less able to maintain consistent interests for long periods.
Keywords: C93; D91; I20; I24; 330; socio-emotional skills; grit; gpas; middle-school students; field experiment; RCT